2014
DOI: 10.4028/www.scientific.net/amr.1030-1032.501
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Chlorination and Adverse Public Health Outcomes in Algeria

Abstract: Drinking water supplies continue to be a major source of human disease because many of them remain unsafe and vulnerable. The aim of this study was to investigate the levels of trihalomethanes formation and chemical and microbiological quality through four raw surface waters as well as finished tap waters. The seasonal changes on trihalomethane formation and concentration of organic precursors were examined. Results show that disinfection for Algerian drinking water reduces the risk of pathogenic infection but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…This is probably largely due to the high levels of chloride and sulphate ions. This is in line with the results of various other studies [6,13,14] indicating the sulphate-chloride type of the waters of the northern Sahara. A cross comparison was also investigated with the local and international drinking water standards for fluoride levels.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is probably largely due to the high levels of chloride and sulphate ions. This is in line with the results of various other studies [6,13,14] indicating the sulphate-chloride type of the waters of the northern Sahara. A cross comparison was also investigated with the local and international drinking water standards for fluoride levels.…”
Section: Resultssupporting
confidence: 93%
“…The studied water samples were found to have a fluoride concentration above the permissible limit for drinking water [7,15]. Many studies showed that fluoride is the result of water-rock interaction and leaching from minerals such as fluorine in various aquifers with different lithologies [1,6,13,14]. In fact, in the studied semi-arid area, groundwater quality is influenced by many different environmental factors such as the lithological nature of the formations, high annual temperature, low precipitations and intense potential evapotranspiration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation